2021
DOI: 10.3390/molecules26123769
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Processing Impact on Alternariol and Aflatoxins of Grape Juice and Fruit Juice-Milk Based Beverages

Abstract: High-pressure processing (HPP) has emerged over the last 2 decades as a good alternative to traditional thermal treatment for food safety and shelf-life extension, supplying foods with similar characteristics to those of fresh products. Currently, HPP has also been proposed as a useful tool to reduce food contaminants, such as pesticides and mycotoxins. The aim of the present study is to explore the effect of HPP technology at 600 MPa during 5 min at room temperature on alternariol (AOH) and aflatoxin B1 (AFB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Similar to what was observed in the present study, HPP was also found to be more effective than thermal treatment for mycotoxins reduction (AFB1 and AOH mycotoxins in juice), obtaining a 12% and 7% decrease for AFB1 and AOH, respectively, in grape juice when thermal treatment was applied without reductions obtained in the rest of juice models (orange juice and strawberry juice/milk beverages) [38].…”
Section: Effect Of Thermal Treatment (Ht) On Enns Contents In the Stu...supporting
confidence: 89%
“…Similar to what was observed in the present study, HPP was also found to be more effective than thermal treatment for mycotoxins reduction (AFB1 and AOH mycotoxins in juice), obtaining a 12% and 7% decrease for AFB1 and AOH, respectively, in grape juice when thermal treatment was applied without reductions obtained in the rest of juice models (orange juice and strawberry juice/milk beverages) [38].…”
Section: Effect Of Thermal Treatment (Ht) On Enns Contents In the Stu...supporting
confidence: 89%
“…High-pressure processing (HPP) is an environmentally friendly technology proposed as useful in reducing food contaminants such as pesticides and mycotoxins [154]. The efficiency of the HPP process depends on processing parameters, the chemical structure of the pesticide or mycotoxin, and the food matrix [154]. For example, its application successfully reduced chlorpyrifos levels in tomato samples under optimized conditions [155].…”
Section: Abiotic Degradation Strategymentioning
confidence: 99%
“…HHP and LP can be considered risk management tools to increase levels of mycotoxins in beverages. The efficiency of pesticide removal by chitosan ranged from 54% to 72% at a chitosan concentration of 0.05% and increased to 86 to 98% when using a higher chitosan concentration (max 0.5%) in comparison to other clarifiers, 0.05% chitosan had the greatest pesticide removal efficiency (72%) [194] Mycotoxins In white wine, OTA was completely removed, whereas red wine had a 40% removal efficiency [196] Patulin (PAT) contamination 1.0 mg/L UV light Thermal procedure…”
Section: Physical Proceduresmentioning
confidence: 99%